Can fungi compete with marine sources for chitosan production? - Ghormade, V. (International Journal of Biological Macromolecules, 2017)
Chitosan, a β-1,4-linked glucosamine polymer is formed by deacetylation of chitin. It has a wide range of applications from agriculture to human health care products. Chitosan is commercially produced from shellfish, shrimp waste, crab and lobster processing using strong alkalis at high temperatures for long time periods. The production of chitin and chitosan from fungal sources has gained increased attention in recent years due to potential advantages in terms of homogenous polymer length, high degree of deacetylation and solubility over the current marine source. Zygomycetous fungi such as Absidia coerulea, Benjaminiella poitrasii, Cunninghamella elegans, Gongrenella butleri, Mucor rouxii, Mucor racemosus and Rhizopus oryzae have been studied extensively. Isolation of chitosan are reported from few edible basidiomycetous fungi like Agaricus bisporus, Lentinula edodes and Pleurotus sajor-caju. Other organisms from mycotech industries explored for chitosan production are Aspergillus niger, Penicillium chrysogenum, Saccharomyces cerevisiae and other wine yeasts. Number of aspects such as value addition to the existing applications of fungi, utilization of waste from agriculture sector, and issues and challenges for the production of fungal chitosan to compete with existing sources, metabolic engineering and novel applications have been discussed to adjudge the potential of fungal sources for commercial chitosan production.
Keywords: Cell wall; Chitin/chitosan; Waste Mycelial Biomass; Zygomycetous Fungi